Designing Energy-Efficient Topologies for Wireless Sensor Network: Neural Approach. (14th December 2010) - Patra, Chiranjib; Guha Roy, Anjan; Chattopadhyay, Samiran; Bhaumik, Parama
Abstract : Preserving energy or battery power of wireless sensor network is of major concern. As such type of network, the sensors are deployed in an ad hoc manner, without any deterministic way. This paper is concerned with applying standard routing protocols into wireless sensor network by using topology modified by neural network which proves to be energy efficient as compared with unmodified topology. Neural network has been proved to be a powerful tool in the distributed environment. Here, to capture the true distributed nature of the Wireless Sensor Network (WSN), neural network's Self-Organizing Feature Map (SOFM) is used.